2019
DOI: 10.3748/wjg.v25.i19.2315
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture at ST36 modulates gastric motility via vagovagal and sympathetic reflexes in rats

Abstract: BACKGROUND Electroacupuncture (EA) at ST36 can significantly improve gastrointestinal symptoms, especially in promoting gastrointestinal motility. The automatic nervous system plays a main role in EA, but few studies exist on how vagovagal and sympathetic reflexes affect EA to regulate gastrointestinal motility. AIM To study the role of vagovagal and sympathetic reflexes in EA at ST36, as well as the associated receptor subtypes that are involved. METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Neurotransmitters, modulators, and pathways of the central nervous system are important factors in the regulation of gastrointestinal motility by EA [32]. e study showed that both GABA and glutamate in the brainstem circuit are involved in the regulation of gastric motility by EA at ST36 [33]. Glutamate is the major excitatory neurotransmitter in the central nervous system and its receptors include both ionotropic receptors and metabotropic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitters, modulators, and pathways of the central nervous system are important factors in the regulation of gastrointestinal motility by EA [32]. e study showed that both GABA and glutamate in the brainstem circuit are involved in the regulation of gastric motility by EA at ST36 [33]. Glutamate is the major excitatory neurotransmitter in the central nervous system and its receptors include both ionotropic receptors and metabotropic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the excitement effect, lower extremity acupoints also suggest an inhibitory effect on GI movement, and the inhibitory rate of ST37/LI11 on gastric movement fluctuates between 6.67%–1.33%[ 58 , 59 ]. Moreover, the effect of ST36 on gastric movement is reversed to inhibition after gene knockout of M2 and M3 receptor subtypes[ 45 ], suggesting the involvement of other receptors. This might be caused by activation of the other vagus pathway, the inhibitory non-adrenergic, noncholinergic (NANC) pathway, whose transmitter is nitric oxide (NO) or vasoactive intestinal polypeptide (VIP), to cause smooth muscle relaxation[ 60 ].…”
Section: Autonomic Nervous System Mechanism Of Acupuncturementioning
confidence: 99%
“…According to a previous study[ 65 ], the abdominal acupoints for gastric motility could be effective within 30 s with a shorter response time, while the acupoint of the hindlimb was effective after 30 s with a longer response time. ST36 showed an excitatory effect in a fast onset manner in sympathectomy rats and β 1&2 knockout mice, suggesting that sympathetic inhibition might be one of the key factors for the delayed onset of ST36 and β1 and β2 receptors may underlie its receptor mechanisms[ 44 , 45 ]. Undoubtedly, the sympathetic pathway is activated by acupoints in the lower limbs; evidence shows that EA at ST36/ST37 increased sympathetic activity in healthy volunteers using a heart rate variability analysis or microneurography evaluation of the left peroneal nerve[ 66 , 67 ].…”
Section: Autonomic Nervous System Mechanism Of Acupuncturementioning
confidence: 99%
See 1 more Smart Citation
“…The regulating effect of acupuncture for gastrointestinal function may be achieved by stimulating nerves, especially vagus nerve. Lu [10] Found that electroacupuncture at ST36 regulated gastric motility in rats through vagus and sympathetic reflex respectively mediated by m2 / 3 and β1 / 2 receptors, and vagus reflex played a major role in this procedure. The results of a research showed that ST36 could stimulate the peroneal nerve, and then transmit the pulse signal to the vagus nerve through the sciatic nerve, release the 1-amino acid decarboxylase and increase the neurotransmitter level [11] .…”
Section: Introductionmentioning
confidence: 99%